Diagnostic and prognostic implications using age- and gender-specific cut-offs for high-sensitivity cardiac troponin T — Sub-analysis from the TRAPID-AMI study. (15th April 2016) - Mueller-Hennessen, Matthias; Lindahl, Bertil; Giannitsis, Evangelos; Biener, Moritz; Vafaie, Mehrshad; deFilippi, Christopher R.; Christ, Michael; Santalo-Bel, Miguel; Panteghini, Mauro; Plebani, Mario; Verschuren, Franck; Jernberg, Tomas; et al.
Abstract: Objectives: To evaluate the impact of age- and gender-specific cut-offs for high-sensitivity cardiac troponin T (hs-cTnT) compared to the general 99th percentile hs-cTnT cut-off on diagnosis and prognosis of acute myocardial infarction (AMI). Methods: 1282 unselected patients presenting to the emergency department with suspected AMI were enrolled as part of the TRAPID-AMI study. In the present sub-analysis, reclassification of AMI diagnosis was performed by comparing the general hs-cTnT cut-off of 14 ng/L to previously proposed age- and gender-dependent hs-cTnT 99th percentile cut-offs (28 ng/L for ≥ 65 years, 9 ng/L for female and 15.5 ng/L for male patients). Patients were further clinically adjudicated into acute coronary syndrome (ACS) and non-ACS. Results: For patients ≥ 65 years, application of age-specified cut-offs resulted in a decrease of AMI from 29.8% to 18.3% in the entire cohort (n = 557) and 54.7% to 40.9% in the ACS subcohort (n = 225). Using gender-specific cut-offs, AMI-rate increased from 16.6% to 22.6% (entire cohort, n = 477) and 62.6% to 71.7% (ACS subcohort, n = 99) in women, whereas in men, rates decreased from 23.1% to 21.1% (entire cohort, n = 805) and 48.8% to 45.9% (ACS, n = 281), respectively. Age-specified cut-offs significantly reclassified patients for outcomes of 1-month and 3-month mortality in the entire and ACS cohort (14.2% net reclassification improvement, p < 0.001, respectively). Contrary, no significant differences in outcomes could be found using gender-specific cut-offs. Conclusions: While influence of gender-specific hs-cTnT cut-offs on diagnostic and prognostic reclassification was only modest in patients with suspected AMI, age-specific cut-offs showed a significant impact and may be considered for further validation.